1999
DOI: 10.1029/1999jd900025
|View full text |Cite
|
Sign up to set email alerts
|

Global emissions of hydrogen chloride and chloromethane from coal combustion, incineration and industrial activities: Reactive Chlorine Emissions Inventory

Abstract: Abstract. Much if not all of the chlorine present in fossil fuels is released into the atmosphere as hydrogen chloride (HC1) and chloromethane (CH3C1, methyl chloride). The chlorine content of oilbased fuels is so low that these sources can be neglected, but coal combustion provides significant releases. On the basis of national statistics for the quantity and quality of coal burned during 1990 in power and heat generation, industrial conversion and residential and commercial heating, coupled with information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
145
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 13 publications
5
145
0
Order By: Relevance
“…8). Although coal combustion used for cooking has been identified as a potential source of chloride emissions (Ianniello et al, 2011;McCulloch et al, 1999), this practice has not been observed in the area. However, chloride species may be emitted from household waste-burning/smoldering, for which particle-bound polychlorinated dibenzo-p-dioxins, dibenzofurans and biphenyls have been measured in previous studies (Gullett et al, 2001;Lemieux et al, 2004;Tue et al, 2016;Zhang et al, 2009), or from sea salt particles subject to high-temperature combustion processes (since this factor is also observed to a lesser extent in the direction of the fishsmoking area).…”
Section: Source Apportionment Of Ommentioning
confidence: 99%
“…8). Although coal combustion used for cooking has been identified as a potential source of chloride emissions (Ianniello et al, 2011;McCulloch et al, 1999), this practice has not been observed in the area. However, chloride species may be emitted from household waste-burning/smoldering, for which particle-bound polychlorinated dibenzo-p-dioxins, dibenzofurans and biphenyls have been measured in previous studies (Gullett et al, 2001;Lemieux et al, 2004;Tue et al, 2016;Zhang et al, 2009), or from sea salt particles subject to high-temperature combustion processes (since this factor is also observed to a lesser extent in the direction of the fishsmoking area).…”
Section: Source Apportionment Of Ommentioning
confidence: 99%
“…Scaling to the current global population of 6 billion suggests that 2000 Tg is an approximate, present global value. If half of this garbage is burned in open fires or incinerators (McCulloch et al, 1999) and it is 50% C, it would add 500 Tg of C to the atmosphere annually. This is about 7% of the C added by all fossil fuel burning (Forster et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of biofuel use has been based on surveys of the rural population and there are not good estimates of how much may occur in urban areas. McCulloch et al (1999) calculated the 1990 garbage production from the 4.5 billion people included in the Reactive Chlorine Emissions Inventory as 1500 Tg. Scaling to the current global population of 6 billion suggests that 2000 Tg is an approximate, present global value.…”
Section: Introductionmentioning
confidence: 99%
“…The major sources of tropospheric HCl in the atmosphere include natural sources from sea salt (Keene et al, 1999) and biomass burning (Andreae et al, 1996), and anthropogenic sources from coal combustion and waste incineration (McCulloch et al, 1999). The global annual emission rates of HCl from sea salt and biomass burning were estimated to be 50 Tg Cl yr -1 (Graedel and Keene, 1995;Keene et al, 1999) and 6 Tg Cl yr -1 (Lobert et al, 1999), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although the emission rates from natural sources are much higher than the anthropogenic counterparts, they are relatively constant and well estimated. The corresponding anthropogenic emission rates from coal combustion and waste incineration were previously estimated to be 4.6 and 2 Tg Cl yr -1 , respectively (McCulloch et al, 1999). Waste incinerations include open waste incineration (the uncontrolled emissions from both residential and dump waste burning) and prescribed waste incineration 5 (the emission from waste incineration plant).…”
Section: Introductionmentioning
confidence: 99%